Plasma levels, pharmacokinetics and dosage regimen of intravenously administered gatifloxacin in buffalo calves (Bubalus bubalis) on coadministration with meloxicam - Dumka, Vinod Kumar; Sandhu, Harpal Singh; Rajput, Neetu (Brazilian Journal of Veterinary Research and Animal Science, 2010)
The pharmacokinetics of intravenously administered gatifloxacin, upon concomitant administration with meloxicam was investigated in buffalo calves. Meloxicam was administered subcutaneously (0.5 mg.kg-1) immediately followed by intravenous administration of Gatifloxacin (4 mg.kg-1). The concentration of gatifloxacin was estimated in plasma by microbiological assay. Pharmacokinetic parameters were calculated and appropriate dosage schedule was computed. The therapeutic plasma drug concentration was maintained up to 12 h. Gatifloxacin was rapidly distributed from blood to tissue compartment, which was evident from the high values of distribution rate constant, α1 (11.9 ± 0.52 h-1) and the ratio of rate constant of transfer of drug from central to peripheral compartments and vice versa, K12/K21 (3.05 ± 0.36) and K13/K31 (2.04 ± 0.12). The area under the plasma drug concentration-time curve and apparent volume of distribution were 12.0 ± 0.68 µg.ml-1.h and 2.69 ± 0.14 L.kg-1, respectively. The elimination half-life (t1/2β), total body clearance (ClB) and the ratio of drug present in peripheral to central compartment (P/C) were 5.59 ± 0.40 h, 337.6 ± 19.9 ml.kg-1.h-1 and 8.04 ± 0.50, respectively. The present study revealed that the most suitable dosage regimen of gatifloxacin when concomitantly administered with meloxicam in buffalo calves would be 2.5 mg.kg-1 followed by 2.0 mg.kg-1 at 12 h intervals.